1998
DOI: 10.1016/s0895-7061(98)00100-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of left ventricular diastolic filling in arterial hypertension Comparison of pulsed doppler echocardiography and acoustic quantification

Abstract: We compared acoustic quantification (AQ) to Doppler echocardiography (DE) in the evaluation of left ventricular (LV) diastolic filling in 41hypertensives and 42 controls. In hypertensives, DE showed reduced ratios of early to late diastolic velocity, AQ revealed reduced peak to late filling rate ratios, and both techniques found prolonged acceleration times indicating abnormal filling. In 22 patients with mild hypertension and less LV hypertrophy, however, all DE filling parameters were normal. In these patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Impaired left ventricular filling in terms of reduced peak filling rate and delayed time to peak filling rate was demonstrated also in arterial hypertension through several studies using RNA, MRI and 2-D echo with automated boundary detection [7,10,12]. In two separate studies it was even suggested to be superior to conventional Doppler echo in detecting early diastolic dysfunction [10,12].…”
Section: Assessment Of Diastolic Function By Vtcmentioning
confidence: 99%
“…Impaired left ventricular filling in terms of reduced peak filling rate and delayed time to peak filling rate was demonstrated also in arterial hypertension through several studies using RNA, MRI and 2-D echo with automated boundary detection [7,10,12]. In two separate studies it was even suggested to be superior to conventional Doppler echo in detecting early diastolic dysfunction [10,12].…”
Section: Assessment Of Diastolic Function By Vtcmentioning
confidence: 99%
“…Spencer et al 20 Chenzbraun et al 17 Angomachalelis et al 15 Muscholl et al 9 abnormal 22% to 48% of the time. The most commonly abnormal LA AQ parameters were the LA diastolic one-third time, as well as the rapid and atrial emptying fractions.…”
Section: Summary Of Published Acoustic Quantification Indices Of LV Dmentioning
confidence: 99%
“…This technique provides LV area or volume versus time waveforms. The diastolic portion of the LV AQ waveform can be used to assess the diastolic properties of the LV 8–18 . We have found that the reliability of AQ for the assessment of LV diastolic function is improved by signal averaging of the continuous data to generate a single averaged waveform 19 .…”
Section: Assessment Of Diastolic Function Using Acoustic Quantificationmentioning
confidence: 99%
See 1 more Smart Citation